National Sovereignty of Thailand to Create Own Brand of Democracy - Anawat Bunnag (Recent Trends in Arts and Social Studies Vol. 5, 2023)
Thailand’s sovereignty is adequately protected against Western meddling and her internal peace is maintained by the cohesiveness of the Thai population, Thailand may finally create her own kind of democracy without fully embracing the capitalist economy. The study shall argue here that the sovereignty of the nation is necessary for Thailand to develop her own version of Democracy based on three assumptions. Rapid economic growth in Thailand has also led to significant use of natural resources, resulting in rising environmental challenges. The first one is based on the premise that full implementation of Western democracy would entail a set of economic values which are contradictory to some Eastern values, and would finally result in the identical chaotic society full of drug abusers and materialistic individuals as has already occurred in the western society. Under the influence of capitalist values, the traditional structure that in the past supported moral principles and upright behaviour is now disintegrating. This virtual communication, which is made up in part of exchanges between people beyond national and cultural boundaries, encourages people to believe that moral principles and upstanding behaviour are merely beliefs and that sometimes breaking them has no negative legal or physical repercussions.The second assumption is based on the claim that demands for democratization in Eastern countries are in fact veiled threats of capitalism. The third assumption contends that the Western democratic model will lessen the morality of the citizen. Thailand could develop her own version of democracy with her own economic system that results from the accumulation and adaptation of Thai traditions and culture.